Определение коэффициентов смещения долбяка при нарезании зубчатых колес планетарного механизма AI - Абрамов, В. А.; Кавецкий, Сергей Николаевич (НТУ "ХПИ", 2006)
В статті розглянуті способи визначення коефіцієнтів зміщення довбяка при нарізанні зубчастих коліс планетарного механизма AI . Наведено блок-схему алгоритма проведення розрахунків.

The methods of determination of displacement coefficients of shaping cutter at cutting of gear-wheels of planetary mechanism are considered in the article AI . The algorithm flow block of conducting of calculations is given.
Keywords: коэффициенты смещения; сателлиты; блокирующие контуры; изолинии; алгоритмы определения коэффициентов